2022
DOI: 10.3390/cancers14225539
|View full text |Cite
|
Sign up to set email alerts
|

USP7 Inhibitors in Cancer Immunotherapy: Current Status and Perspective

Abstract: Ubiquitin-specific protease 7 (USP7) regulates the stability of a plethora of intracellular proteins involved in the suppression of anti-tumor immune responses and its overexpression is associated with poor survival in many cancers. USP7 impairs the balance of the p53/MDM2 axis resulting in the proteasomal degradation of the p53 tumor suppressor, a process that can be reversed by small-molecule inhibitors of USP7. USP7 was shown to regulate the anti-tumor immune responses in several cases. Its inhibition imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
0
8
0
1
Order By: Relevance
“…Therefore, components in the ubiquitin pathway have been proposed as potential targets for treatment strategies for diseases and cancer ( 37 , 38 ). USP7 is one of the most abundant USPs and plays a multifaceted role in many cellular events, including carcinogenic pathways ( 39 - 42 ). A study has found that USP7 is a promising target for cancer treatment by regulating the MDM2/MDX-p53 pathway ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, components in the ubiquitin pathway have been proposed as potential targets for treatment strategies for diseases and cancer ( 37 , 38 ). USP7 is one of the most abundant USPs and plays a multifaceted role in many cellular events, including carcinogenic pathways ( 39 - 42 ). A study has found that USP7 is a promising target for cancer treatment by regulating the MDM2/MDX-p53 pathway ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…After nine months of immunotherapy, these correlations changed dramatically, and all symptoms for those patients with a complete response were alleviated almost completely. It is known that cancer-related fatigue is a common symptom, and its prevalence reaches 80 to 90% of cancer patients under treatment [ 31 , 32 ]. Fatigue symptoms are often under-diagnosed and under-treated by health care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are necessary to elucidate the detailed localization and extracellular functions of the ubiquitin-conjugating enzyme complex, including E1, E2, and E3, during fertilization of the ascidian H. roretzi. Although genome editing experiments of E1, E2, and E3 would be difficult due to the inability of culturing a juvenile into a sexually matured adult in an aquarium, several specific inhibitors against the UPS [ 33 ], including deubiquitinating enzyme [ 34 , 35 ], may give us an answer to the questions remained to be solved.…”
Section: Discussionmentioning
confidence: 99%